ANALISIS EARNING PER SHARE DAN HARGA SAHAM - Nanu Hasanuh (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
This study aims to determine the effect of Earning Per Share (EPS) on stock prices partially or simultaneously on banking companies listed on the Indonesia Stock Exchange for the period 2012-2016. The independent variable in this study is Earning Per Share (EPS). The dependent variable in this study is the Stock Price. Sampling was done by purposive sampling method, with a total sample of 7 (seven) companies and 35 observational data. The research method used is a quantitative method with a descriptive and verification approach. The results showed that Earning Per Share (EPS) significantly affected stock prices.